SURVIVAL STUDY ON DATA STORAGE AND TRANSACTION SECURITY USING AUTHENTICATION TECHNIQUES - Kavitha, K; Saravanan, V (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is information technology (IT) model that allows the ubiquitous access to shared pools of configurable system resources and higher-level services provisioned with lesser effort. Cloud computing provides number of advantages in information technology. Cloud storage is an essential service of cloud computing that are prevalent as it present low-cost and on-demand utilization of large storage and processing resources. Security is an essential barrier to comprehensive prevalence of cloud computing. Security is mainly prioritized portion for any cloud computing environment during data storage and data transaction. Cloud computing approach is linked with users sensitive data stored both at client’s end and cloud servers. For improving the security level, authentication techniques are used for allowing the authenticated user to access the data. But, complexity of the security is high when decentralization of data over the wide area of network. In addition, existing methods failed to improve the authentication accuracy and data confidentiality. Our main objective of the work is to improve the security level during the data storage and data transaction by using cryptosystem techniques